MODEL MANAJEMEN KOMUNIKASI FRONT OFFICE E-GOVERNMENT SEBAGAI MEDIA PELAYANAN PUBLIK (STUDI PADA SITUS PEMERINTAH DAERAH KOTA/KABUPATEN DI YOGYAKARTA) - Edwi Arief Sosiawan; Susilastuti DN (Jurnal Ilmu Komunikasi, 2008)
On the challenges of development for democratization and transparency in the frame- work of regional autonomy, local governments now compete to build a race-e-government in- frastructure. In factual, the main obstacles of the implementation of e-government is on the governance or management structure of the management and Quantity and quality of human resources at government agencies that are very limited. The object of the selected study site is the city of Yogyakarta, Sleman regency government sites and the Government of Bantul district. The formulation of the problem is taken “How Communication Model Management Front Of- fice E-Government as a Public Service Media Site on the regional government of Yogyakarta, Sleman District Government Sites Site and the Government of Bantul Regency? “ Research method used is descriptive research to guide the inductive eksploratori to the results of research that the technical provisions of the respective websites of local governments to become the object of research in managing the front office has to follow some standard that is required in the development of the web as a medium for communication and information. Up toditas informa- tion, especially news on the navigation was done routinely. But still there is a delay of up toditas websites is a sign that there is imbalance between the management of websites each local gov- ernment. Number of links the information of each local government websites have been suffi- cient, meaning that many categories of information provided. The fundamental problem lies in the fact that the government does not provide e-mail links for the user community, if there is acceptance of the feedback is to the manager or administratur websites and not on the officials concerned.